The Effects of Riluzole on Cisplatin-induced Ototoxicity - Üstün Bezgin, Selin; Uygur, Kadir Kemal; Gökdoğan, Çağıl; Elmas, Çiğdem; Göktaş, Güleser (International Archives of Otorhinolaryngology, 2019)
Introduction Riluzole (2-amino-6-trifluoromethoxy benzothiazole) is known as a neuroprotective, antioxidant, antiapoptotic agent. It may have beneficial effects on neuronal cell death due to cisplatin-induced ototoxicity.Objective To evaluate the effect of riluzole on cisplatin-induced ototoxicity in guinea pigs.Methods Twenty-four guinea pigs, studied in three groups, underwent auditory brainstem response evaluation using click and 8 kHz tone burst stimuli. Subsequently, 5 mg/kg of cisplatin were administered to all animals for 3 days intraperitoneally (i.p.) to induce ototoxicity. Half an hour prior to cisplatin, groups 1, 2 and 3 received 2 ml of saline i.p., 6 mg/kg of riluzole hydrochloride i.p., and 8 mg/kg of riluzole hydrochloride i.p., respectively, for 3 days. The auditory brainstem responses were repeated 24 hours after the last drug administration. The cochleae were analyzed by transmission electron microscopy (TEM).Results After drug administiration, for 8,000 Hz stimulus, group 1 had significantly higher threshold shifts when compared with groups 2 (p < 0.05) and 3 (p < 0.05), and there was no significant difference in threshold shifts between groups 2 and 3 (p > 0.05). Transmission electron microscopy findings demonstrated the protective effect of riluzole on the hair cells and the stria vascularis, especially in the group treated with 8 mg/kg of riluzole hydrochloride.Conclusion We can say that riluzole may have a protective effect on cisplatin- induced ototoxicity. However, additional studies are needed to confirm these results and the mechanisms of action of riluzole.
Keywords: riluzole; cisplatin; ototoxicity; auditory brainstem response; transmission electron microscopy